Efeitos da suplementação com probióticos sobre a microbiota intestinal e parâmetros cardiometabólicos em mulheres hipertensas: um estudo clínico randomizado, triplo cego e controlado por placebo - Silva, Larissa de Fátima Romão da (2020)
Systemic arterial hypertension is considered the main risk factor for the development of cardiovascular diseases and its etiology seems to be linked to sympathetic hyperactivity. Studies have shown that intestinal dysbiosis can play a fundamental role in the development of arterial hypertension since the composition of the intestinal microbiota affects the cardiovascular, immune, neural and metabolic systems. Thus, the use of probiotics has emerged as a therapeutic strategy with the potential to treat hypertension. In this sense, the present study aims to evaluate the effects of supplementation with a probiotic mixture on cardiovascular parameters, anthropometric, biochemical, food consumption variables and the composition of fecal microbiota in hypertensive women. This is a randomized, triple-blind, placebo-controlled clinical trial, conducted with 40 hypertensive women aged between 20 and 50 years. Patients were randomized into two groups: probiotic group- (n = 20) treated with 1g / of a probiotic mixture containing Lactobacillus paracasei Lpc-37 R SD 5275 R, Lactobacillus rhamnosus HN001 R SD 5675 R, Lactobacillus acidophilus NCFM R SD 5221 R , Bifidobacterium lactis HN019 R SD 5674 and placebo group (n = 20) treated with 1 g / day of polydextrose for 8 weeks, respectively. Biochemical tests, blood pressure assessment, heart rate variability, anthropometric assessment, food consumption and fecal microbiota count were performed before and after the intervention for 8 weeks. Weight, BMI and waist circumference were similar between the two groups (p> 0.05). Probiotic supplementation significantly reduced fasting glycemia (-10.3 mg / dL range, p <0.05) and cholesterol levels (-23.4 mg / dL range, p <0.05) and increased HDL-cholesterol (range 6.5 mg / dL, p <0.05) compared to baseline condition. Probiotic supplementation resulted in higher Lactobacillus fecal counts (p <0.05) and reduced the number of patients with bacterial overgrowth of the small intestine by 67%. Probiotic supplementation reduced systolic BP by 5 mmHg and diastolic BP by 2 mmHg in hypertensive women, and reduced LF oscillation and the LF / HF ratio (p <0.05) in the frequency domain of heart rate variability. Probiotic supplementation for 8 weeks had beneficial effects on fasting blood glucose levels, lipid profile, intestinal microbiota and autonomic modulation in hypertensive women.